Towards the management, conservation, marketing and utilization of bamboos : proceedings of the seminar - National Bamboo Seminar (1992 : Kuala Lumpur); Wan Razali Wan Mohd; Aminuddin Mohammad (Kuala Lumpur : FRIM, 1994)
28